Pengaruh Online Review terhadap Brand Image di UNP Hotel & Convention Center Padang - Nur Fadillah; Violintikha Harmawan (Pusat Penelitian Dan Pengabdian Masyarakat STIEPARI Semarang, 2025)
The objective of this study is to analyze online reviews and brand image at Unp Hotel & Convention Center Padang. The study is motivated by the fact that UNP Hotel Convention has a considerable potential due to several factors that are exceptionally supportive for accommodation. The study uses quantitative methods and the type of research used in this study is associative causal or cause and effect relationships. The data obtained from survey results was separated into respondents who were the objects of research. The influence of the Online Review variable on Brand Image has a sample mean value of 0.744, a tstatistics value of 30.942> 1.96, and a p value of 0.000 <0.05. As a result, there is a positive and significant influence of the Online Review variable with Brand Image, so H1 is accepted.